2006
DOI: 10.1117/12.655659
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring photoresist dissolution in supercritical carbon dioxide using a quartz crystal microbalance

Abstract: New lithographic techniques are being implemented to help further reduce feature sizes in microelectronics. A technique for the development of standard commercial extreme ultraviolet (EUV) photoresists in a carbon dioxide compatible salt (CCS) and supercritical carbon dioxide (scCO 2 ) solution is being investigated to reduce line edge roughness and image collapse of high aspect ratio features. 1, 2 To understand the kinetics and overall mechanism of photoresist dissolution into the high pressure CCS/scCO 2 so… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2007
2007
2009
2009

Publication Types

Select...
2
1

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 22 publications
(24 reference statements)
0
8
0
Order By: Relevance
“…Complete details of the QCM apparatus and development procedure were discussed in detail elsewhere. 3 The cell temperature and pressure were monitored with a thermocouple and pressure transducer. Previous results have shown that the CCS development rate is directly proportional to temperature 5 , and that complete photoresist removal in less than one minute is possible at 80°C 4 .…”
Section: Development Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…Complete details of the QCM apparatus and development procedure were discussed in detail elsewhere. 3 The cell temperature and pressure were monitored with a thermocouple and pressure transducer. Previous results have shown that the CCS development rate is directly proportional to temperature 5 , and that complete photoresist removal in less than one minute is possible at 80°C 4 .…”
Section: Development Proceduresmentioning
confidence: 99%
“…3,4 This paper addresses what effects using a preconditioning CO 2 drying step before development and using a hexamethyldisilazane (HMDS) adhesive coating have on the photoresist removal rate and the effectiveness of photoresist removal.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…QCM apparatus: (A) CO 2 cylinder, (B1−B5) valves, (C) syringe pump with water jacket, (D) preheating coil, (E) pressure transducer, (F) QCM high pressure cell, (G) thermocouple, (H) stand, (I) circulator and heater for water bath, (J) water bath, (K) phase lock oscillator, (L) frequency counter, (M) signal conditioning connector block, (N) computer, (O) feed through connection, (P) high pressure feed through, (Q) O-ring, and (R) quartz crystal. , …”
Section: Methodsmentioning
confidence: 99%
“…One technique that achieves reduction of both pattern collapse and LWR utilizes supercritical carbon dioxide (scCO 2 ) and a carbon dioxide compatible salt (CCS) to develop standard EUV photoresists. The CCS/scCO 2 one-step development process takes advantage of the low surface energy of scCO 2 to help prevent image collapse and the plasticizing properties of CO 2 in the polymer to help reduce LWR. The effects of temperature, mass transfer, pressure, and CCS concentration on photoresist removal rate were previously explored using a high pressure quartz crystal microbalance (QCM) . The QCM studies in this paper provide details of adsorption, absorption, and diffusion behavior of CO 2 and the CCS at 35 and 50 °C.…”
Section: Introductionmentioning
confidence: 99%